Pengaruh Good Governance dan Sistem Pengendalian Intern Pemerintah (SPIP) Terhadap Pencegahan Fraud Dengan Akuntabilitas Sebagai Variabel Mediasi - Putri Aprilia; Irfan Sophan Himawan (AKUNTANSI 45, 2024)
Good governance procedures that are implemented properly can avoid opportunities for fraud to occur. In addition, preventing fraud can be done by implementing the Government Internal Control System (SPIP). The purpose of this study is to explain the influence of the government’s internal control system through accountability for fraud. The types of data used are primary data and secondary data. The data collection technique was carried out by distributing 60 questionnaires. The population in this study were all village officials in the Cibitung sub-district. The data analysis technique uses multiple linear regression analysis techniques and path analysis with the help of the SPSS version 26 program. The results of this study indicate that good governance has an effect on fraud while the government internal control system (SPIP) has no effect on fraud, good governance has an effect on fraud through accountability and the government’s internal control system (SPIP) influences fraud through accountability.